796 Chronic Pneumoperitoneum: Cause or Consequence of Pneumatosis Cystoides Intestinalis. (12th October 2021) - Baggaley, A; Clements, C; Gerogiannis, I; Bloom, I
Abstract: Pneumatosis cystoides intestinalis (PCI), 'gas cysts' in the wall of the bowel, is a rare sign that can be found as a result of many different conditions, ranging from benign and asymptomatic, to life threatening. Its pathogenesis is not yet fully understood, and patients found to have PCI are treated in a heterogeneous manner. Pneumoperitoneum, however, is much more commonly seen by the General Surgeons, and most often occurs as a result of a perforated viscus; usually necessitating an emergent surgical intervention. Spontaneous pneumoperitoneum occurs very rarely, although it is seen more frequently with small bowel PCI, compared to large bowel PCI. We present here an unusual case of a patient with acute-on-chronic pneumoperitoneum and subsequently subacute small bowel obstruction associated with small bowel pneumatosis cystoides intestinalis. The patient also had extensive pan colonic and jejunal diverticulosis, although the area of perforation and PCI was discrete and located in the mid-ileum. It is unclear whether the patient had chronic pneumoperitoneum secondary to perforated PCI, or if the PCI developed secondary to an ileum perforation of unknown origin (fitting with the bacterial or mechanical theory of pathogenesis). The patient went onto to have an emergency laparotomy and small bowel resection 28 months after initial presentation and a trial of conservative management.